Communication Strategy Of Al-Washliyah Branch Management In Empowering Coastal Communities In Panai Tengah District, Labuhanbatu Regency - Restilia, Tuti; Muktarruddin, Muktarruddin; Mailin, Mailin (UNIVERSITAS PAKUAN, 2024)
Communication strategy in empowering which society conditions public coast in Panai Tengah District, Regency Labuhanbatu with income depending on nature that is work as fishermen, laborers plantations, laborers farmers, traders and government employees. Diverse economy this is in empowering Al- washliyah with a social religion approach for society empowered and purposeful achieved the program of activities education regardless of ignorance and freedom thinking as well as good understanding _ seen in the form of memorization program paragraph short, tahfidz program, memorize move it prayer and its meaning as well as putting it into practice. Da'wah training program lecture empowering alumni as teachers at al- washliyah and getting public benefit Because students attending school is public Central Panai District. Increase empowerment use social media to help development and school facilities , building connections Good to society, do activity social compensation child orphans, routine studies at the al- washliyah and mandorsah prayer rooms muslimat with communication persuasiveness of teachers and students in school and human relations to public discuss to find solutions to existing problems. Warning day al- washliyah birthdays and Islamic celebrations were held